The Effect of Giving Teacher Motivation on Student Learning Outcomes - Reska Anggara; Sahade Sahade; Fajriani Azis (Universitas Negeri Makassar, 2023)
This study aims to determine the effect of teacher motivation on student learning outcomes in class X accounting expertise program at SMK Negeri 1 Makassar. The variable in this study is the provision of teacher motivation as the independent variable and learning outcomes as the dependent variable. The population in this study were all students of class X accounting expertise program at SMK Negeri 1 Makassar. The sampling technique used was proportionate stratified random sampling, with a sample of 58 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive percentage analysis, instrument test consisting of validity and reliability testing, hypothesis testing consisting of simple linear regression analysis, Pearson product moment correlation analysis, coefficient of determination, and t-test using SPSS version 25 for windows. Based on the results of data analysis that has been carried out, a simple linear regression equation model is obtained Y = 50,907 + 0.413X, which means that for each additional 1 unit of teacher motivation, learning outcomes experience an increase of 0.413. From the results of the analysis of the coefficient of determination (r2), the value of r2 = 0.499, this means that the influence of teacher motivation on learning outcomes is 49.9% and the remaining 50.1% is influenced by other factors. Meanwhile, based on the results of the Pearson product moment correlation analysis, the correlation coefficient is 0.706 and is in the strong category, which means that there is a strong relationship between teacher motivation and student learning outcomes of class X accounting expertise program at SMK Negeri 1 Makassar. Meanwhile, the results of the t-test analysis obtained a significant value of 0.000 <0.05, which means that teacher motivation has a significant effect on learning outcomes, thus the hypothesis is accepted.